APLIKASI PEMBELAJARAN KUANTUM SEBAGAI UPAYA UNTUK MENINGKATKAN PRESTASI BELAJAR PENDIDIKAN AGAMA HINDU DAN BUDI PEKERTI SISWA KELAS I SEMESTER I TAHUN PELAJARAN 2017/2018 SD NEGERI 3 GADUNGAN - Ni Wayan Kompiang Ekawati (LP3M Universitas PGRI Mahadewa Indonesia, 2021)
Student achievement in the subjects of Hindu Religion and Moral Education will not be low. However, in reality, the initial data acquisition as a result of observations made found the fact that the learning achievement of class I students in the first semester of the 2017/2018 academic year only reached 68.64. These results are still very far from the minimum standard for achieving the quality of education with the KKM 75 set at SD 3 Gadungan. The purpose of this classroom action research is to improve the learning achievement of Hindu Religious Education and Morals for Class I Semester I Elementary School 3 Gadungan School Year 2017/2018 after the implementation of the Quantum learning model in learning. This classroom action research involves 11 research subjects conducted in two cycles through the stages of planning, implementation, observation and reflection. Learning achievement test is a tool used in collecting research data which is then analyzed using descriptive analysis. The results obtained from this study indicate an increase in the ability of students to follow the learning process from the initial average of 68.64 to 74.56 in the first cycle and increased to 81.55 in the second cycle with 45% early learning completeness in the first cycle. to 73% and in the second cycle increased to 91%. The conclusion that can be drawn from these results is that the implementation of the Quantum learning model can improve the learning achievement of Hindu Religion and Moral Education in first grade students of SD Negeri 3 Gadungan in the 2017/2018 academic year.